Characterisation of Thai strawberry (Fragaria × ananassa Duch.) cultivars with RAPD markers and metabolite profiling techniques. (December 2020) - Sirijan, Mongkon; Drapal, Margit; Chaiprasart, Peerasak; Fraser, Paul D.
Abstract: Strawberries ( Fragaria  ×  ananassa Duch.) are one of the most economically important fruit crops worldwide, several commercially viable cultivars are cultivated in the northern region of Thailand. The morphological characters at the young vegetative seedling stage can be very similar, which has hindered breeding efforts. The present study assesses the ability of random amplification of polymorphic DNA (RAPD) markers and metabolomics techniques to distinguish six strawberry cultivars. Both techniques showed congruent results for the leaf tissue and classified the cultivars into three major clusters. For the most different cultivars, Akihime and Praratchatan No.80, fruits were analysed at eight fruit ripening stages. The data highlighted a broad biological variation at the early ripening stages and less biological variation at the mature stages. Key metabolic differences included the polyphenol profile in Praratchatan No.80 and fatty acid synthesis/oxidation in Akihime. In summary, the RAPD and metabolite data can be used to distinguish strawberry cultivars and elucidate the metabolite composition of each phenotype. This approach to the characterisation of genotypes will benefit future breeding programmes. Graphical abstract: Image 1 Highlights: RAPD markers and metabolite profiles of strawberry leaves showed similar clustering. Strawberry fruit showed high biological variation at green compared to red-ripe stage. Fruit metabolism varied between Praratchatan No.80 and Akihime during ripening. Fatty acid metabolism/catabolism of Akihime results in distinct aroma profile. Praratchatan No.80 has >2-fold higher levels of polyphenols and flavonoids.